A Systematic Analysis on Secondary School English Teachers’ Scientific Articles - Kurniasih, Esti; Fahri; Pusparini, Ririn; Lestari, Lies Amin; Savitri, Wiwiet Eva; Aminin, Zainul; Ariyanti, Lisetyo (PROJECT (Professional Journal of English Education), 2025)
As professional teachers, teachers are expected to be able to produce scientific works by conducting research, not only experimental but also classroom action research (CAR). Henceforth, from their research, they are expected to be able to produce a scientific article and publish it in reputable national or international journals. Due to the importance of scientific articles for the teachers’ career, therefore, this study aims to describe the profile of secondary school English teachers’ competencies in writing a scientific article. By using a rubric adapted from CARS model, it was found out that they still got many difficulties in writing a good scientific article. Those difficulties cover constructing and developing the introduction section which comprises general background information about the phenomenon being investigated, the results of relevant previous studies and theoretical framework, research gaps, novelty, and research objectives; elaborating the research method and discussion which refers to the results of relevant theories and previous studies; and neglecting the use of the last ten-year references. Regarding those unsatisfactory results, therefore, it is strongly suggested for the them to learn deeper by having more practices and trainings or workshops on conducting research and writing scientific articles as the output of their research.